AN ANALYSIS OF ENGLISH CODE MIXING USED BY AGNEZ MO - Endriani Salamat; Tini Mogea; Mister Gidion Maru (SoCul: International Journal of Research in Social Cultural Issues, 2021)
This investigation focuses on Agnez Mo's statements. The researchers employ the descriptive approach to conduct this study. Researchers employ the documentation approach to obtain data. Hoffman's theory, included intra-sentential code mixing, intra-lexical code mixing, and pronunciation modification, is used to examine the data. After evaluating the video, the researchers come up with a total of 87 data. The most common category is intra-sentential, which accounts for 73 % of all data, followed by intra-lexical, which accounts for 14 % of all data, and finally, change pronunciation, which accounts for just 1 % of all data. Agnez Mo employs code-mixing for four reasons, according to the researchers: talking about a specific issue, being enthusiastic about something, interjection, and displaying group identification. The majority of the evidence shows that the parts of speech are nouns.